2020
DOI: 10.32553/jbpr.v9i1.711
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Profiles and Biological Properties of Cymbopogon Citratus, Cymbopogon Giganteus, Cymbopogon Shoenanthus, and Their Isolated Compounds: A Review

Abstract: Essential oils are worldwide used for their several biological properties. As such, the genus Cymbopogon is an interesting source of essential oils. Among the genus Cymbopogon, the most studied plant species, especially in West Africa, are C. citratus, C. giganteus and C. Schoenanthus. The essential oils extracted from these plants are sought for their various properties such as their insecticidal, analgesic, anti-inflammatory, antioxidant, hypotensive properties. Their anti-leishmaniasis, antimicrobial, antip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…Similarly, A. indica seed oil accelerated the growth of F. verticillioides on stored corn (Fandohan et al, 2004). The fungicidal effect of F1 would then increase with the dose of the treatment applied and more precisely with the dose of its constituents such as limonene, Z-Mentha-1(7),8-dien-2-ol, E-Mentha-1(7),8-dien-2-ol, E-p-Mentha-2,8-diene-ol and Z-p-Mentha-2,8-diene-1-ol (Bossou et al, 2020). This hypothesis corroborates the results of another study where it was shown that 1.0 μL/mL of C. citratus essential oil with 79% citral was more fungicidal than that with 68.4% citral (Martinazzo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, A. indica seed oil accelerated the growth of F. verticillioides on stored corn (Fandohan et al, 2004). The fungicidal effect of F1 would then increase with the dose of the treatment applied and more precisely with the dose of its constituents such as limonene, Z-Mentha-1(7),8-dien-2-ol, E-Mentha-1(7),8-dien-2-ol, E-p-Mentha-2,8-diene-ol and Z-p-Mentha-2,8-diene-1-ol (Bossou et al, 2020). This hypothesis corroborates the results of another study where it was shown that 1.0 μL/mL of C. citratus essential oil with 79% citral was more fungicidal than that with 68.4% citral (Martinazzo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%